AI-Augmented Threat Detection in Identity Federation Systems : Enhancing Security Through Intelligent Monitoring - Aditi Mallesh, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the application of artificial intelligence to enhance threat detection in identity federation systems, addressing critical security challenges posed by the complex, interconnected environments of modern enterprises. Identity federation, while offering streamlined user access across multiple platforms, creates unique security vulnerabilities that traditional approaches struggle to mitigate. Conventional security methods—including rule-based detection, static access controls, and perimeter-focused models—lack the adaptability and contextual awareness needed to protect federated environments effectively, often resulting in high false positive rates, limited visibility across trust boundaries, and slow response to sophisticated attacks. The article examines how AI-based technologies—including deep learning for sequential pattern analysis, natural language processing for communication analysis, and contextual anomaly detection—can transform security monitoring in federated environments. A comprehensive system architecture is presented, featuring integrated data collection, processing and analysis, and decision and response layers that work in concert to provide dynamic, adaptive protection. The article emphasizes the importance of continuous learning mechanisms that enable security systems to adapt to evolving threats and organizational changes. A detailed case study from the financial services sector demonstrates the practical implementation and significant security improvements achieved through AI-augmented threat detection, including reduced detection time, decreased false positives, and enhanced analyst efficiency. While implementation challenges exist, including data quality issues, privacy considerations, and specialized expertise requirements, this article contributes valuable insights for organizations seeking to strengthen security postures while maintaining the operational benefits of federated identity environments.
Keywords: Identity Federation Security; Artificial Intelligence; Behavioral Analysis; Anomaly Detection; Adaptive Security